Reporting quality and risk of bias of randomized controlled trials of Chinese herbal medicine for multiple sclerosis - Wu, Jing-Ying; Yang, Jiang-Li; Hu, Jia-Ling; Xu, Shan; Zhang, Xiao-Jie; Qian, Shi-Yan; Chen, Min-Li; Ali, Mahad Abdulkadir; Zhang, Juan; Zha, Zheng; Zheng, Guo-Qing (Frontiers in Immunology, 2024)
Background: Multiple sclerosis (MS) is the most common non-traumatic disabling disease affecting young adults. A definitive curative treatment is currently unavailable. Many randomized controlled trials (RCTs) have reported the efficacy of Chinese herbal medicine (CHM) on MS. Due to the uncertain quality of these RCTs, the recommendations for routine use of CHM for MS remain inconclusive. The comprehensive evaluation of the quality of RCTs of CHM for MS is urgent. Methods: Nine databases, including PubMed, Embase, Web of Science, Cochrane Library, EBSCO, Sinomed, Wanfang Database, China National Knowledge Infrastructure and VIP Database, were searched from inception to September 2023. RCTs comparing CHM with placebo or pharmacological interventions for MS were considered eligible. The Consolidated Standards of Reporting Trials (CONSORT) and its extension for CHM formulas (CONSORT-CHM Formulas) checklists were used to evaluate the reporting quality of RCTs. The risk of bias was assessed using the Cochrane Risk of Bias tool. The selection criteria of high frequency herbs for MS were those with cumulative frequency over 50% among the top-ranked herbs. Results: Twenty-five RCTs were included. In included RCTs, 33% of the CONSORT items and 21% of the CONSORT-CHM Formulas items were reported. Eligibility title, sample size calculation, allocation concealment, randomized implementation and blinded description in CONSORT core items were reported by less than 5% of trials. For the CONSORT-CHM Formulas, the source and authentication method of each CHM ingredient was particularly poorly reported. Most studies classified the risk of bias as “unclear” due to insufficient information. The top 5 most frequently used herbs were ordinally Radix Rehmanniae Preparata, Radix Rehmanniae Recens, Herba Epimedii, Scorpio and Poria. No serious adverse effect had been reported. Conclusions: The low reporting of CONSORT items and unclear risk of bias indicate inadequate quality of RCTs in terms of reporting completeness and result validity. The CONSORT-CHM Formulas appropriately consider the unique characteristics of CHM, including principles, formulas, and Chinese medicinal substances. To improve the quality of RCTs on CHM for MS, researchers should adhere more closely to CONSORT-CHM Formulas guidelines and ensure comprehensive disclosure of all study design elements.